Contemporary trends in accounting, finance and financial institutions : proceedings from the International Conference on Accounting, Finance and Financial Institutions (ICAFFI), Poznan 2016 /: proceedings from the International Conference on Accounting, Finance and Financial Institutions (ICAFFI), Poznan 2016. ([2018]) - Unknown
No abstract available